2017
DOI: 10.1016/j.prevetmed.2016.12.011
|View full text |Cite
|
Sign up to set email alerts
|

A real-time reporting system of causes of death or reasons for euthanasia: A model for monitoring mortality in domesticated cats in Taiwan

Abstract: A novel, real-time mortality recording system was designed to collect mortality data in companion animals from veterinary hospitals in Taiwan. This retrospective study aims to introduce the system, and to utilize the data collected for further investigation of the lifespan and mortality of the domesticated cat population stratified by demographic variables. Our data revealed that 1325 domesticated cats were acquired between 2012 and 2014. The median age of the study population was 8.0 years (IQR 3.0-13.0; rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Studies in several countries have reported the most common diseases leading to death or euthanasia in pet cats. Cause of death/euthanasia in cats younger than five years are predominantly due to trauma or viral and respiratory disease, whereas death/euthanasia in older cats, such as our cohort, are mainly related to renal disease, neoplasia, cardiovascular disorders, or non-specific illness [ 37 , 38 ]. Thus, our findings of rate and causes of cat mortality in our unowned urban cat population managed with TNR differ little from those commonly cited in relation to owned cat populations.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in several countries have reported the most common diseases leading to death or euthanasia in pet cats. Cause of death/euthanasia in cats younger than five years are predominantly due to trauma or viral and respiratory disease, whereas death/euthanasia in older cats, such as our cohort, are mainly related to renal disease, neoplasia, cardiovascular disorders, or non-specific illness [ 37 , 38 ]. Thus, our findings of rate and causes of cat mortality in our unowned urban cat population managed with TNR differ little from those commonly cited in relation to owned cat populations.…”
Section: Discussionmentioning
confidence: 99%
“…Disappearance or death, most often due to motor vehicle trauma, have been reported as common outcomes for stray cats (14, 23, 28). Accidental death is also generally the most common cause of mortality reported for companion cats with outdoor access, particularly younger cats (7072). Cats who suffer significant injury or death, may simply disappear and so, cat welfare assessments are not necessarily a good way of evaluating environmental risks to welfare, particularly for stray cats (as their whereabouts may be less likely to be closely monitored compared to companion cats).…”
Section: Discussionmentioning
confidence: 99%
“…Trauma was the third most common reason for ICU admission in a Canadian feline population, with an associated mortality rate of 19.2% . In a survey of 1325 cats in Taiwan, trauma was the fifth most common cause of death or reason for euthanasia . Trauma scores assist in the characterization of patient populations for clinical research and may have application in patient triage and hospital or clinician performance benchmarking .…”
Section: Introductionmentioning
confidence: 99%